ANALISIS BENTUK-BENTUK DEIKSIS DALAM NOVEL DAUN PUN BERDZIKIR KARYA TAUFIQURRAHMAN AL-AZIZY - Sameth, Fira Firanty; Aria Bayu Setiaji; Susi Hardila Latuconsina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Deixis is one of the branches of pragmatics that functions to indicate persons, places, and times whose references depend on the context of an utterance. The use of deixis is not only found in spoken communication but also in literary works, including novels. Daun Pun Berdzikir by Taufiqurrahman Al-Azizy was selected as the object of this study because it contains various forms of deixis that contribute to the development of the storyline and relationships among characters. This study aims to describe the forms of deixis found in the novel. The research employed a qualitative approach using a descriptive method. The data consisted of words, phrases, clauses, and sentences containing deixis in the novel Daun Pun Berdzikir. Data were collected through reading, note-taking, and documentation techniques, while data analysis was conducted by identifying, classifying, and describing the forms of deixis based on George Yule’s theory. The findings revealed 874 instances of deixis, consisting of 813 person deixes, 16 place deixes, and 45 time deixes. Person deixis was the most dominant type, comprising 247 first-person deixes, 168 second-person deixes, and 398 third-person deixes. In conclusion, the use of deixis in Daun Pun Berdzikir is predominantly characterized by person deixis, which functions as a marker of participants in speech events.